CT Perfusion as a Selection Tool for Mechanical Thrombectomy, a Single-Centre Study. Issue 1 (20th January 2020) - De Muynck, Emilie; Huybrechts, Vincent; Hemelsoet, Dimitri; Dhondt, Elisabeth; Vanlangenhove, Peter; Defreyne, Luc
Background: Recently, CT perfusion (CTP) has been proposed as a selection tool for stroke patients to be treated with endovascular thrombectomy. We investigated whether functional outcome following endovascular treatment was improved after the introduction of CTP. Methods: This retrospective single-centre study includes all patients with a major vessel occlusion in the anterior circulation that received a CTP and underwent a mechanical thrombectomy from 2014 up to 2015. CTP were visually evaluated. Demographics, stroke and time data, procedural data, functional outcomes as measured by the modified Rankin Scale (mRS) and the association between these variables were studied. A comparison was made with the results of a similar local retrospective study from before the CTP "era". Results: Eighty-nine patients were included in this study. Median National Institutes of Health Stroke Scale (NIHSS) was 16 (Interquartile range 6). At three months, good functional outcome (GFO; mRS 0–2) was achieved in 48.4% and excellent functional outcome (EFO; mRS 0–1) in 34.4% of patients. The mortality rate at three months was 14.5%. GFO at one year was 44.8%, EFO was 31.3% and mortality 21.1%. The duration of the thrombectomy procedure and the EFO were associated (p = 0.032). The outcome improvement achieved with CTP was higher compared to the reference study (GFO 48.4% versus 44%; EFO 34.4% versus 29%) but remained below the statistical significance. Conclusions: Mechanical thrombectomy for anterior circulation strokes based on CTP did not result in a significant functional outcome improvement. The duration of the thrombectomy procedure was the sole time-interval related to improved functional outcome.